HUBUNGAN SIKAP KERJA DUDUK DENGAN KEJADIAN NYERI PUNGGUNG BAWAH PADA KARYAWAN INEWS TV - Fadilla Wina Savana (2022)
Background: Lower back pain is a perceived disorder that is influenced by individual and occupational risk factors. Low back pain disorders are often found in the work environment, especially in workers who carry out activities with inappropriate or less ergonomic postures and body positions. Work attitude is an action taken by workers in their work. Purpose: This study was to determine whether there is a relationship between sitting posture and the incidence of lower back pain in iNews TV employees. Methods: This research is descriptive using a cross-sectional study approach. The sample from the study was selected using a purposive sampling technique with the inclusion and exclusion criteria of respondents so that a sample of 24 employees was obtained. Results: Pearson correlation bivariate analysis was used to determine the relationship between sitting posture and the incidence of lower back pain (p = 0.019). This study shows that there is a significant relationship between sitting posture and the incidence of lower back pain in iNews TV employees. Conclusion: Based on the results of the study, it shows that attention is needed and changes in work attitudes for the better